IMPLEMENTATION OF TRANSFORMATIONAL LEADERSHIP TO INFLUENCE AFFECTIVE COMMITMENT THROUGH PERCEIVED ORGANIZATION SUPPORT - Nasution, Nurhafiza Aini; Fahruzi, Alwi; Rusmewahni, Rusmewahni; Dewi, Kumala Vera (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This research aims to analyze the influence of transformational leadership on affective commitment through perceived organizational support at the Tebing Tinggi City Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Office. The research method uses path analysis with partial least squares - Structural Equation Model (SEM - PLS) on 40 employee respondents. The research results show that transformational leadership has a positive and significant effect on affective commitment and perceived organizational support. Apart from that, perceived organizational support also has a positive and significant effect on affective commitment. These results indicate that perceived organizational support mediates the effect of transformational leadership on affective commitment. These findings provide important implications for human resource management practitioners in increasing employee commitment and performance through the development of transformational leadership and perceived organizational support. Keywords: Transformational Leadership, Affective Commitment, Perceived Organization Support